The Effect on skin papillomas by administration of Fruits of Momordica dioica extract in DMBA/Croton oil induced benign cancer in mice (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Skin papillomas are not cancerous, but they can trigger an inflammatory disorder and irritate the area where the wart is present. The study was to find natural agents that prevent and/or cure skin papillomas. The fruits of Momordica dioica have been known to contain potent phytoconstituents that have anti-inflammatory, cardiovascular, diabetic, oncological, and other health benefits. To investigate inhibition of skin papilloma’s by administration of a fruit extract of Momordica dioica in DMBA/Croton oil-induced benign cancer in mice. Induction of papilloma’s by topical application of DMBA/Croton oil for 4-5 weeks; after confirmation of papilloma's, the Momordica dioica and 5-Flu10 mg/kg were administered. Body weight, tumor incidence, cumulative number of tumors, tumor yield, average latency time period, number of papillomas, hematological parameters, antioxidant enzymes, and pro-inflammatory cytokines were measured. 100% tumor incidence was observed in DMBA/croton oil, whereas the other groups except the normal control had quite a similar tumor incidence. The cumulative number, tumor yield, and average latent period have significantly improved with the treatment in skin papilloma mice. Hematological markers and NLR (< 3.0) have improved (p<0.001), which is indicative of reduced acute systemic inflammation. The deviations on LPO and CAT from baselines were corrected by Momordica dioica and found to have a significant impact on their levels (p<0.001). Post-treatment of immunosuppressive markers such as; TGF-beta (p<0.001), TNF-alpha (p<0.001), and IL-6 (p<0.001) were decreased significantly and increased the levels of IFG-g (p<0.001), which correlates with increased immune activation. Hence, the intake of fruits of Momordica dioica inhibits the growth of skin papillomas.